Network disruption detected in BD (Bangladesh) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Bangladesh. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: BD-2026-0003. Severity: critical. Confidence: 70%